Normal climatological water balance in the microregion of alto teles pires - MT - Hurtado de Mendoza Borges, Pedro; Hurtado de Mendoza Morais, Pedro; Morais dos Santos Hurtado de Mendoza, Zaíra; Navarro Bezerra, Diandro (Seven Editora, 2023)
The microregion of Alto Teles Pires, in the Mato Grosso State, is located at an important national pole of irrigation by center pivot systems, whose municipalities have presented relevant agricultural production. Thus, the management of water resources for consumptive uses in agricultural activities in this geographical area deserves special attention.  Among the main tools for the management of water resources, the climatological water balance can be mentioned since it makes it possible to establish a relationship between the input of water from precipitation and its storage capacity in the soil.  This theme motivated the realization of this research, which aimed to carry out the climatological water balance for the municipalities of this microregion. The study used historical series of hourly and daily meteorological data, obtained from the National Institute of Meteorology.  The reference evapotranspiration was estimated using the Penman-Monteith-FAO. The climatic data were analyzed by the  EXCEL spreadsheet, determining the main daily descriptive statistics of each variable, as well as the monthly averages of precipitation and evapotranspiration.  Then, the climatological water balance was performed with its graphic representation of excess or deficiency of water and its alterations.  The volume of precipitation and total annual evapotranspiration in Sorriso was around 10% and 2% higher than estimated, respectively, for the municipality of Nova Ubiratã. However, in the municipality of Sorriso, the volume of precipitation was greater than evapotranspiration, while in Nova Ubiratã there was an inversion of this relationship, resulting in a water deficit throughout the year.  The monthly climatological water balance made it possible to define the year with excess and deficiency of water in the soil, as well as the beginning and end of its withdrawal and replacement for the municipalities of the referred microregion.  Therefore, estimating the mentioned balance is a useful and viable tool for planning agricultural activities. The results obtained in this research showed that the soil class, the climatic conditions, given by the type of biome and geographic location, and the size and period of collection of the historical series of meteorological data can influence the climatological water balance. DOI: https://doi.org/10.56238/alookdevelopv1-002